Stabilization of third-order differential equation by delay distributed feedback control - Alexander Domoshnitsky; Shirel Shemesh; Alexander Sitkin; Ester Yakovi; Roman Yavich (Journal of Inequalities and Applications, 2018)
Abstract There are almost no results in mathematical literature on the exponential stability of third-order delay differential equations. One of the main purposes of the paper is to fill this gap. We propose an approach to the study of stability for third-order delay differential equations. On the basis of these results, new possibilities of stabilization by delay feedback input control are proposed.